Leadership: communication skills and a balanced ideological flow among students as an initial pillar to national leadership / Zanirah Mustafa@Busu ... [et al.] - Mustafa@Busu, Zanirah; Mohd Nasir, Irfan Amier; Nik Din, Nik Muniyati; Awang @ Ab Rahman, Nurul Hidayah; Noor Zainan, Nurul Izzah; Ismail, Mohd Khairul Anuar; Junoh, Noraini; Mat Jusoh, Nor Asmira; Yusuf, Norazmila (Faculty of Communication & Media Studies, 2022)
A leader is valued through how he behaves and acts in his leadership through communication. One of the most important is the ability of a leader to make decisions and implement a plan through his ideology to develop an organization. A decision is born of a thought process. Communication and significant ideas of students are important starters for the progress of national leadership to produce leaders who have good communication competitiveness as well as thoughtful ideas for progress not only for national leadership but also world leadership. examining the communication methods and ideological streams of students that can be the best product of the country's leadership in the future. The aim of this study is also to find out the mastery of communication skills as well as the presentation of thoughtful ideas among UiTM Kelantan students for national leadership. Communication skills studied include interpersonal communication skills, intrapersonal communication skills and non -verbal communication skills. Methodological methods of library research, documentation, observation, research, and interviews to students were used to gather relevant information. The majority of students are now very focused on learning solely with the aim of achieving an excellent average grade, it is undeniable that it is very accurate and the main purpose for students who are undergraduates, but as balanced and competitive students, they must be able to reach a level as someone who is a leader and is able to loudly convey their golden ideas. Therefore, to achieve the desire to build the identity of students who are able to communicate and think about leadership, various approaches and plans should be worked on. Effective communication skills actually require seriousness, experience and interest in the profession or field they are involved in later. In addition, it can enhance positive values to improve students' social and emotional skills.